Elevated cerebrospinal fluid protein in POLG‐related epilepsy: Diagnostic and prognostic implications. (19th June 2018) - Hikmat, Omar; Naess, Karin; Engvall, Martin; Klingenberg, Claus; Rasmussen, Magnhild; Tallaksen, Chantal M. E.; Brodtkorb, Eylert; Fiskerstrand, Torunn; Isohanni, Pirjo; Uusimaa, Johanna; Darin, Niklas; Rahman, Shamima; et al.
Summary: Objective: Epilepsy is common in individuals with mutations in POLG, the gene encoding the catalytic subunit of the mitochondrial DNA polymerase gamma. Early recognition and aggressive seizure management are crucial for patient survival. Disruption of the blood‐brain barrier (BBB) is implicated in various neurological disorders including epilepsy. The aim of this study was to assess whether POLG ‐related disease is associated with BBB dysfunction and what clinical implications this has for patients. Methods: Our retrospective study used data from 83 patients with pathogenic POLG mutations from 4 countries––Norway, Sweden, Finland, and the United Kingdom. Data were collected using a structured questionnaire. We used the presence of raised cerebrospinal fluid (CSF) protein and a raised CSF/serum ratio of albumin (Q‐alb) to evaluate the integrity of the blood‐CSF barrier. Results: Raised CSF protein was found in 70% of patients (n = 58/83) and appeared to be associated with the most severe phenotypes. In those in whom it was measured, the Q‐alb ratio was markedly elevated (n = 18). The majority of those with epilepsy (n = 50/66, 76%) had raised CSF protein, and this preceded seizure debut in 75% (n = 15/20). The median survival time from symptom onset for those with raised CSF protein was decreased (13 months) compared to those with normal CSF protein (32 months). Significance: Our results indicate that there is disruption of the BBB in POLG ‐related disease, as evidenced by a raised CSF protein and Q‐alb ratio. We also find that raised CSF protein is a common finding in patients with POLG disease. Our data suggest that the presence of BBB dysfunction predicts a poorer outcome, and elevated CSF protein may therefore be an additional biomarker both for early diagnosis and to identify those at high risk of developing epilepsy.